Implementasi Metode Multi-Objective Optimization On The Basis Of Ratio Analysis dalam Seleksi Mahasiswa Program Indonesia Pintar - Abdul Karim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The Smart Indonesia Program (PIP) is assistance in the form of cash, expanding access, and learning opportunities from the government which are given to students and students who come from poor or vulnerable families to finance education. This study uses decision support system techniques with the Multi-Objective Optimization method basically of Ratio Analysis (MOORA) which can help in determining a good ranking. Criteria for Rapot Score, Parents' Income, Achievement, Place of Residence, PKH Recipients, KKS Participants. The results of applying the MOORA method of selecting the Smart Indonesia Student Selection Program are types with a value of 0.191937493 in Alternanip A10